Inovasi Produk MP-ASI Berbasis Jamur Tiram untuk Peningkatan Diversifikasi Usaha dan Gizi Anak pada UMKM Omah Jamur Hijrah Sampang - Cucun Setya Ferdina; Kristian Triatmaja Raharja; Elisa Christiana; Subkhan Umam Amrulloh; Ishrokiyah Ofi Maulidina (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
Indonesia is a developing country with a significant nutritional problem. Improving nutrition during the first thousand days of life will support growth and development, from pregnancy to age 2. Complementary feeding (MP-ASI) can be prepared from nutrient-dense, relatively affordable and readily available ingredients. One example is using local oyster mushroom ingredients. The partner in this Community Partnership Empowerment (PKM) program is Omah Jamur Hijrah, located in Sampang. This activity covers various important aspects, such as processing and packaging based on nutritional value. Each activity in this program aims to address the challenges faced by partners. The methods and steps to achieve this goal include: Focus Group Discussions (FGDs), workshops, technology implementation assistance, and supervision. The program's outcomes include: 1) increased partner knowledge; 2) practical skills; 3) product innovation, including the creation of an MP-ASI product, instant baby porridge based on oyster mushroom flour. The program's sustainability is expected to be enhanced to encourage the continued application of these skills.